Analisis Perlindungan Hukum Atas Kerugian Investor Publik Akibat Praktik Insider Trading Berdasarkan Hukum Positif Indonesia - Yosia Clementino Moningka; Ariawan Gunadi (UNES Law Review, 2023)
This article is motivated by the rapid development of the world of capital markets in Indonesia, and it cannot be denied that one of the crimes occurring in the world of capital markets is the practice of insider trading. This research uses a normative juridical approach, namely a type of approach that examines or analyzes secondary data such as library materials or secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. Regulations regarding the practice of insider trading already have a legal umbrella in Article 95 and Article 99 of Law Number 8 of 1995 concerning Capital Markets, but in fact the existence of a legal umbrella with these articles still creates unclear implementation and law enforcement regarding insider trading cases. happened in Indonesia. Situations like this then contribute to losses felt by other public investors. Therefore, this research will discuss legal protection arrangements and legal remedies for public investors who experience losses due to insider trading practices based on Indonesian positive law. This research uses a normative juridical method with the Statute Approach. Legal protection for public investors for losses resulting from insider trading practices is regulated as immaterial losses which can take legal action through litigation, namely civil lawsuits with the argument of unlawful acts, or non-litigation through the Alternative Institution for Financial Services Sector Dispute Resolution which is provided by OJK.